Molecular Epidemiology of GI.3 Norovirus Outbreaks from Acute Gastroenteritis Surveillance System in Taiwan, 2015–2019. (13th February 2020) - Chiu, Shu-Chun; Hsu, Jia-Kai; Hu, Szu-Chieh; Wu, Ching-Yi; Wang, Ying-Chin; Lin, Jih-Hui
Abstract : Norovirus is the leading cause of food-borne disease outbreaks. We conducted this study to examine the incidence and molecular characteristics of norovirus genogroup I infections from acute gastroenteritis outbreaks in Taiwan. Between January 2015 and June 2019, 2121 acute gastroenteritis clusters were reported to Taiwan CDC, of which 351 (16.5%) clusters were positive for NoV GI, and GI.3 was the most prevalent (36.8%) during the study period. The GI.3 infections were significantly higher than non-GI.3 infections in the age groups of 0–5 and 6–18 years. The phylogenetic analysis of the MCC tree revealed that VP1 genes were divided into 3 groups: the GI.P3-GI.3 strains in Taiwan were genetically close to Japan and the GI.Pd-GI.3 strains were segregated into 2 other groups which were genetically closely related to China. In addition, 7 GI.Pd-GI.3 recombinants were identified circulating in Taiwan between 2018 and 2019, and the prevalence of GI.Pd-GI.3 should be monitored to assess whether this could become the new predominant strains in neighboring Asian countries or other parts of the world. Both GI.P3-GI.3 and GI.Pd-GI.3 strains cocirculate, the recombination among these two lineages occurs frequently, contributing to the genetic diversity and multiple occurrences of different norovirus lineages, and their rapid evolution makes future control more difficult. Continued surveillance and timely interventions are critical to understand the complexity of norovirus gene variation and to monitor the new emerging norovirus strains.